149k views
4 votes
Solve the system by substitution.
--5x - 9y = 33
-Y - 1 = x

User Sivakanesh
by
4.7k points

1 Answer

6 votes

Answer:

(12/7, -19/7)

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define systems

--5x - 9y = 33

-y - 1 = x

Step 2: Simplify systems

5x - 9y = 33

-y - 1 = x

Step 3: Solve for y

  1. Substitute: 5(-y - 1) - 9y = 33
  2. Distribute 5: -5y - 5 - 9y = 33
  3. Combine like terms: -14y - 5 = 33
  4. Isolate y term: -14y = 38
  5. Isolate y: y = -19/7

Step 4: Solve for x

  1. Define: -y - 1 = x
  2. Substitute: -(-19/7) - 1 = x
  3. Simplify: 19/7 - 1 = x
  4. Subtract: 12/7 = x
  5. Rewrite: x = 12/7

And we have our final answer!

User KURRU HEM
by
5.1k points